Critical Analysis of the Possible Determining Factors of COVID-19 Epidemiological Trend in Bangladesh: A Review - Ahmed, Asif; Rahman, Mohammad Mahmudur (Bangladesh Journal of Infectious Diseases, 2022)
Since its first report on March 08, 2020, COVID-19 positive cases and number of deaths have increased which reached the peak in late June and started to decline slowly in late August in Bangladesh. COVID-19 transmission and disease progression depends on multifaceted determinants e.g. virus genetics, host immunity, social distancing, co-morbidity, socio-demographic and environmental parameters. Therefore observed epidemiological trend may not follow predicted models and thus warrant detail investigation of the contributing factors. In this perspective, in the light of literature we hypothesize that preventive intervention strategies, socioeconomic limitations, climatic and meteorological indexes, acquired immunity of Bangladeshi population, demographic characteristics, health indicators and food habits contributed toward the observed COVID-19 trend. The key limiting factor was number of diagnostic tests in getting real epidemic scenario. Strong immunity of young people compared to the elderly and low prevalence of non-communicable diseases might have kept most of them asymptomatic, less severe with silent recovery. Climatic parameters, less population density in rural areas and certain food habits perhaps helped to restrict and combat the infection up to a level. Genetic polymorphism can also be driving factor in disease progression. Despite several helpful determinants in Bangladesh, person to person contact is still the leading risk factor for COVID-19 transmission. Infection may increase rapidly if safe distance and preventive measures are not strictly followed especially in the coming winter. Expansion of test capacity, intelligent work and vacation planning and public awareness should continue to reduce the infection rate and disease catastrophe. Bangladesh Journal of Infectious Diseases June 2021;8(1): 36-41